Conjunctive Relation in English Advertisement on Child and Teen Magazines - Arifah, Nur; Djatmika, Djatmika; Santosa, Riyadi (Indonesian Journal of EFL and Linguistics, 2019)
There are many previous types of research about semiotics, language style and image in analyzing advertisements. This study analyzes advertisements by conjunctive relations. This is aimed at observing how the conjunctive relation analyzing the advertisement and constructing the meaning to target readers. This study describes the use of conjunctive relation that results from different stages in the advertisement. The data used advertisements published from August – September 2018 in Junior and Teen Magazine. The method of this study is descriptive qualitative. This study used purposive based sampling based on the objectives of the study. In analyzing data, researchers use Systemic Functional Linguistics approach. This step of analysis uses a domain, taxonomy, componential and cultural theme analysis. The study finds out that the advertisement is structured by exposition genre and the message is delivered well to specific target readers; children or teenagers. Besides,conjunctive relation’s analysis finds the invitation meaning explicitly. In conclusion, the language and meaning are easy to understand both the target readers.